Strengthening National Defense: Dynamics of Mandatory Biodiesel Policy and Renewable Energy Potential in Indonesia's Palm Oil Industry - Mohamad Ikhwan Syahtaria (Universitas Padjadjaran, 2023)
Palm oil, a valuable natural resource, has emerged as a viable component of new renewable energy endeavors. Since 2006, the Indonesian government has harnessed this resource's potential by converting crude palm oil (CPO) into Fatty Acid Methyl Ester (FAME), a key constituent of biodiesel when blended with fossil fuels. Minister of Energy and Mineral Resources Regulation No. 12/2015 laid the foundation for the mandatory biodiesel policy, which, facilitated by the Badan Pengelola Dana Kelapa Sawit (BPDPKS) financing mechanism, has been operational for five years. This investigation delves into the policy's mechanics, evaluating its readiness for international markets, the challenges it confronts, and its potential to attain energy independence and augment the nation's economic prowess. Employing a qualitative approach and descriptive methodology, this study concludes: 1) Mandatory Biodiesel implementation adheres to the stipulations of Minister of Energy and Mineral Resources No. 12/2015, yet certain policy directions exhibit overlap; 2) Indonesian biodiesel grapples with the implications of RED II, projected global biodiesel utilization reductions, and US policies aimed at diminishing biodiesel consumption, implying a sustained need for incentives; 3) Energy independence, a central aspiration of the mandatory biodiesel program, remains an aspiration yet to be realized.